Scientific production in collaborative networks in the field of Education Policy in Brazil (2000 - 2014) - Isac Pimentel Guimarães (Red Latinoamericana de Estudios Epistemológicos en Política Educativa, 2018)
This study investigated the relationship between the standards of scientific production and the academic education policy, through the struggles generated between the different positions of agents in collaborative networks, in the field of Education Policy and Management in the Graduate Programs in Education from the Northeast Region of Brazil, in a 15-year period (2000-2014). Therefore, supported by the sociological doing and by the scientific field theory of Pierre Bourdieu, the paper emphasizes the agents that produce a scientific and institutionalized academic representation of the theme as well as the social conditioning of their practice. Methodologically, it sought to establish the structure of the academic production space through the use of statistical tools. The results pointed out that the organization of the education policy field revolves mainly around the struggles between peers regarding scientific authority. This occurs because achievements linked to the scientific production have great importance in the scientific publication market, where the research results gain visibility inside education graduate program and become credits in the scientific community, which are consequently, traded by other credits in collaborative networks.